Genetic dissection of Drosophila adenylate cyclase. - Livingstone, M S (1985)
The Drosophila learning mutant rutabaga is missing calcium/calmodulin activation of adenylate cyclase (EC4.6.1.1). The mutation was mapped at a finer resolution to X chromosome bands 12F5-7. By comparing wild-type and mutant cyclase activities, the relative responsiveness of the calcium-sensitive and calcium-insensitive components to different ligands could be determined; the calcium-sensitive fraction of the total cyclase activity was significantly less responsive to guanyl nucleotides and monoamines. The results suggest that the component of cyclase activity that is stimulated by calcium/calmodulin, possibly a genetically distinct catalytic subunit, is not coupled to the G subunit or the G subunit/monoamine receptor complex.